Unusual records of waterbirds in Costa Rica: possible connection to El Niño 2015-2016 - Sandoval Vargas, Luis Andrés (2016)
These records were reported during the winter migrations in 2015 and 2016; five of the six species were apparently migrating from their reproductive sites in North America to their wintering grounds on the Pacific coast of South America (Burger & Gochfeld 1996, Chandler 2009). However, the ENSOs of 2015–2016 were the strongest on record, and they displaced the Humboldt Current to the north (Instituto Meteorológico Nacional 2015). As a consequence, pelagic species such as the Red Phalarope and Sabine’s Gull, which winter mainly in the Humboldt Current (Burger & Gochfeld 1996, Chandler 2009) and are known to occur farther north, accidentally came closer to shore (Murphy 1936). The ENSO also significantly decreased Costa Rican precipitation (Waylen et al. 1998), reducing, and in some cases, eliminating the availability of coastline wetlands (pers. obs.). This may have driven species such as Wilson’s Phalarope and Stilt Sandpiper to move away from their regular migratory routes in search of adequate habitats.